Malaysian perspective on Malaysia-China relations and the bilateral educational exchanges between Malaysia and China - Xia, Nan; Lee, Yok Fee; Adnan, Zatul Himmah (Universiti Putra Malaysia Press, 2019)
Malaysia and China have established formal diplomatic relations since 31 May 1974. The bilateral relations between Malaysia and China are well developed in the economic and trade fields, followed by tourism. Therefore, there are many records and studies on these aspects. However, in a recent development, the bilateral relation in the field of education has become more and more important, thus the bilateral educational exchanges between Malaysia and China has become the focus of this writing. This article has two main objectives, firstly, to elaborate the background of Malaysia-China relations; and secondly, to examine the achievement of educational exchange between Malaysia and China since 1974, especially on the higher education aspect. Primary data for this study were collected through interviews and a total of ten informants were selected based on purposive sampling and snowball sampling. Meanwhile, secondary data were collected from journal articles, reports, and websites. Both data were analyzed using content analysis. The findings of this study indicate that, due to the ideological issue, Malaysia and China did not have any actual contact until 1989 when the issue of the Communist Party of Malaya was solved. However, the development of Malaysia-China relations was initially slow until the rise of China and the promotion of the "Belt and Road Initiative," when the relations between the two countries entered the most splendid period in history. Nevertheless, the rapid development of Malaysia-China relations has caused some controversial voices among Malaysians. Malaysia and China began to conduct educational cooperation officially after they signed a Memorandum of Understanding (MOU) on education cooperation in 1997. In addition, mutual recognition of academic higher education qualifications was finally resolved when the two countries signed the Framework Agreement to Facilitate Mutual Recognition in Academic Higher Education Qualifications in 2011. Today, it is believed that the educational exchange between Malaysia and China has become better and more significant.